HUBUNGAN ANTARA PENGETAHUAN DAN PEKERJAAN IBU DENGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI 7-12 BULAN DI PUSKESMAS SELINCAH KOTA JAMBI - LIZA (Universitas Adiwangsa Jambi, 2020)
According to World Health Organization (WHO) explains that giving breastfeeding to babiesaged 0 to 6 months without the other supplement. Based on the result of a research, knownthat international guidance recommend to giving exclusive breastfeeding during early sixmonth based on scientific paper about benefit of breastfeeding for baby live immune, theirgrowth and breast feeding gives all of energy and nutrition needed baby during early 6month. Files of Jambi health breastfeeding profile that baby get exclusive breastfeeding asmany as 36,94% on 2011, increase to 62,6% on 2012. Purpose of this research is to knowthe relationship[ between mother’s knowledge and job with giving breastfeeding to baby inSelincah Health Center Jambi on 2020. This method is analytic survey with cross sectionalapproach. Population in this research is all of mothers with their age 7-12 months babies,that come to selincah Health Center jambi on February 17-22 with 35 respondent as sampleby accidental sampling. Analysis use univariate and bivariate analysis using Chi-Squarestatistic test with computerization with significant level α = 0,05 result of 35 respondents withgiving exclusive breastfeeding 51,4% and un giving 48,6%. Mother with good knowledge asmany as 57,1% and less knowledge 42,9%. Working mothers as many as 28,6% and unworking mothers 71,4%. Result of bivariate analysis show that there’s significant relationshipbetween knowledge with giving exclusive breastfeeding where p value 0,002 and nosignificant relationship between jobs with giving exclusive breastfeeding, where p value1,000. From this research hoped that health worker do counseling on safe breastfeeding forworking mothers so that working have the same opportunity to provide exclusivebreastfeeding